The Great Terror on steroids: exploring the counterfactual scenario of artificial intelligence-driven purges under Stalin - Varajidás, Henrique (Frontiers in Political Science, 2025)
For self-evident reasons of historical synchrony, most research probing the frontiers between totalitarianism studies and artificial intelligence studies to date has centered on mass surveillance in Xi Jinping’s China. The Great Terror on Steroids, an exercise in experimental Political Science grounded on a version of the historical-contextual analysis method adapted to support counterfactual reasoning, takes an entirely different approach. Namely, the article explores the counterfactual hypothesis of what difference it could have made if the perpetrators of a key part of the Stalinist Soviet Union’s Great Terror—specifically, the campaign targeting “Trotskyists” in the Party—had had at their disposal an artificial intelligence tool modeled after the cutting-edge technology utilized in predictive policing today. We start by reviewing totalitarianism and artificial intelligence studies, with a focus on their potential intersections. Next, we describe our method, including its promise and limitations. Then, we introduce the Great Terror as a case study. Subsequently, we delve into our research question in detail, process-tracing the origins, background, setup, dynamics, and results of the aforementioned campaign and deducing the advantages and drawbacks that the use of the predictive policing artificial intelligence tool would likely have brought to its design and implementation. We conclude that, on the “positive” side, the selection of targets would have been more neutral in the sense that literally everyone could become one for reasons that would have been almost entirely out of the arbitrary hands of the perpetrators and that the brutal interrogation sessions and inter-related snowballing effects would have been substantially minimized. On the other side, nonetheless, we reckon that enhanced neutrality would in no way have equated with enhanced rationality since, owing to its inherent defects, the tool would not have been able to rid the process of the dark shadow of entirely irrational detentions and escalatory paranoia. Finally, we come to conjecture that the Stalinist leadership would probably have preferred the historical version of the purge due to the key human mobilization functions that the artificial intelligence-boosted version would have precluded.